FROM HISTORICAL MEANING TO DYNAMIC ECOLOGICAL SIGNIFICANCE: A MA'NA-CUM-MAGHZA READING OF Q. 30:41 AND Q. 7:56 IN THE CONTEXT OF INDONESIA'S CLIMATE CRISIS - Akhmad Aidil Fitra; Suprizen Suprizen; Muhammad Hafidz Kusnadin; Riri Maiyati; Idi Warsah (Magister Ilmu Al-Qur'an dan Tafsir UINSU Medan, 2026)
Indonesia's escalating climate crisis marked by massive deforestation, peatland fires, rising temperatures, and sea-level threats constitutes not merely a techno-political problem but a profound ethical and theological crisis demanding serious engagement from Islamic scholarly traditions, including Qur'anic exegesis. This study aims to construct the dynamic ecological significance (maghza) of Q. 30:41 and Q. 7:56 within the context of Indonesia's climate crisis, employing Sahiron Syamsuddin's Ma'na-cum-Maghza approach a hermeneutical method that first excavates the authentic historical meaning (ma'na) of the text before developing its significance for the contemporary context. Employing qualitative library research methodology, the study draws on classical tafsir works al-Ṭabarī, Ibn Kathīr, al-Zamakhsharī, al-Rāzī and contemporary exegeses M. Quraish Shihab, Sayyid Quṭb, Ibn ʿĀshūr as primary sources, complemented by scientific data on Indonesia's climate crisis from IPCC AR6 (2023) as knowledge helper. Historical ma'na analysis reveals that Q. 30:41 functions as a diagnostic-causal verse affirming ecological fasād as a direct consequence of human agency (kasb al-nās), while Q. 7:56 functions as a prescriptive-normative verse mandating the preservation and restoration of iṣlāḥ al-arḍ as a non-negotiable theological trust. The maghza construction finds that fasād fī al-barr wa al-baḥr constitutes a theological equivalent of anthropogenic ecological destruction confirmed by modern climate science, while iṣlāḥ represents an active mandate for ecological restoration as a realization of khalīfah stewardship. This study contributes three dimensions of novelty: methodological, as the first systematic application of Ma'na-cum-Maghza to Indonesia's climate crisis; substantive, through the integration of Qur'anic hermeneutics with ecological scientific data; and contextual, by strengthening global Islamic eco-theology discourse from a Nusantara scholarly perspective.